A model for international spillovers to emerging markets - Romain Houssa; Jolan Mohimont; Christopher M. Otrok (National Bank of Belgium, 2019)
This paper develops a small open economy (SOE) dynamic stochastic general equilibrium (DSGE) model that helps to explain business cycle synchronization between an emerging market and advanced economies. The model captures the specificities of both economies (e.g. primary commodity, manufacturing, intermediate inputs, and credit) that are most relevant for understanding the importance as well as the transmission mechanisms of a wide range of domestic and foreign (supply, demand, monetary policy, credit, primary commodity) shocks facing an emerging economy. We estimate the model with Bayesian methods using quarterly data from South Africa, the US and G7 countries. In contrast to the predictions of standard SOE models, we are able to replicate two stylized facts. First, our model predicts a high degree of business cycle synchronization between South Africa and advanced economies. Second, the model is able to account for the influence of foreign shocks in South Africa. We are also able to demonstrate the specific roles these shocks played during key historical episodes such as the global financial crisis in 2008 and the commodity price slump in 2015. The ability of our framework to capture endogenous responses of commodity and financial sectors to structural shocks is crucial to identify the importance of these shocks in South Africa.
Keywords: E3; E43; E52; C51; C33; 330; Macroeconomic Policies; Emerging Markets; SOE; DSGE; Bayesian; Foreign shocks; monetary policy